Lecturers' and Students' Perceptions of MBKM: The MBKM Curriculum Implementation Journey - Dewirahmadanirwati Dewirahmadanirwati; Agustina Agustina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study addresses the specific research problem of examining the preparedness of lecturers and students for the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum, focusing on critical insights and challenges. The research methodology involved surveys conducted among lecturers and students, aiming to gauge their awareness, engagement, and perceptions regarding MBKM activities. Students in the Management Study Program presented varying perspectives, with 45 out of 53 respondents actively preparing for MBKM. However, 5 students felt unprepared, and 3 expressed disinterest. Survey results regarding the impact of MBKM program implementation on the student learning process reveal positive outcomes. A substantial 37% reported good learning improvement, 43% very good, and 20% excellent. In terms of perception, 78% of students anticipated the program's positive contribution to broadening perspectives and enhancing competencies. However, 19% remained uncertain, and 3% claimed ignorance, suggesting a need for targeted communication strategies to address uncertainties. The study further delves into the barriers to MBKM program implementation in the Management study program. Curriculum adjustment emerged as a significant hurdle for 59% of respondents, with funding and partner exploration concerns at 32% and 52%, respectively. Additionally, 37% faced challenges adjusting academic information systems, while 13% each identified regulations and information gaps as obstacles. These findings underscore the multifaceted nature of challenges, emphasizing the necessity for comprehensive strategies to address curriculum, funding, partnerships, and information system adjustments for a successful MBKM program implementation.